2022
DOI: 10.21315/apjee2021.36.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Self-Generated Online Projects in an ELT Class at a Thai University during the COVID-19 Pandemic

Abstract: This paper reports how self-generated online projects were integrated into an English language teaching (ELT) class at a Thai university and their impact on pre-service teachers’ experience during the unexpected COVID-19 situation. A qualitative approach was used to describe the integration of self-generated online projects as final group projects and report the learners’ opinions towards their online project-based learning. The participants were 58 pre-service English language teachers who took the Linguistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Through the collaboration, they added that students' problem-solving and critical thinking were also developed. In the same breath, Poonpon (2021) found that integrating a selfgenerated online project improved the students' motivation, problem-solving, and teamwork skills. Additionally, it enhanced their digital and teaching abilities.…”
Section: Introductionmentioning
confidence: 91%
“…Through the collaboration, they added that students' problem-solving and critical thinking were also developed. In the same breath, Poonpon (2021) found that integrating a selfgenerated online project improved the students' motivation, problem-solving, and teamwork skills. Additionally, it enhanced their digital and teaching abilities.…”
Section: Introductionmentioning
confidence: 91%
“…It can be seen that the number of studies conducted in 2020 is very low compared to 2021 and 2022; this may be the impact of the disruption of educational activities in countries during the period when the COVID-19 pandemic took place most explosively. However, after a certain adaptation period and to meet the learning needs during the COVID-19 pandemic, online PjBL studies have been accelerated in the years 2021-2023 (Paristiowati et al, 2022;Poonpon, 2021;Prasetiyo et al, 2023;Rusmini et al, 2021;Schina et al, 2021;Tsybulsky & Muchnik-Rozanov, 2023;Yustina et al, 2020).…”
Section: Publication Yearmentioning
confidence: 99%
“…Duration of the study conducting the intervention or the time of pre-service teachers learning with the PjBL approach of the included articles varied quite widely, ranging from two weeks (Chung & Li, 2021) to a year (Kamali Arslantas & Kocaoz, 2021; Lee & Galindo, 2021), takes place in the years from 2019 to 2022. In which most of the included articles, this process takes place in about one-two semesters (no less than 16 weeks), including Al-Busaidi and Al-Seyabi (2021), Alromaih et al (2022), Brown and Jain (2020), Elfeky et al (2022), Habibi et al (2022), Hernández-Barco et al (2021, Huo et al (2021), Lin et al (2021), Martinez (2022), Poonpon (2021), Schina et al (2021), Tsybulsky and Muchnik-Rozanov (2023), Van Loi and Hang (2021), and Yustina et al (2020). The remaining studies had durations ranging from two to 15 weeks.…”
Section: Durationmentioning
confidence: 99%
See 2 more Smart Citations